Therapeutic patterns and outcomes in older patients (aged ≥ 65 years) with stage III inoperable non-small cell lung cancer (NSCLC): An investigational study from the SEER database - Wangyan Zhong; Hang Yuan; Ting Li; Xueying Jin (PLoS ONE, 2025)
Purpose Currently, optimal treatment regimens for older patients with stage III inoperable NSCLC remain unclear. The aim of this retrospective study was to investigate therapeutic patterns and survival outcomes in older patients with stage III inoperable NSCLC who received radiation therapy (RT) alone or combined with chemotherapy (CT). Methods A retrospective analysis was conducted on 5740 patients aged ≥65 years with stage III inoperable NSCLC, using data from the Surveillance, Epidemiology, and End Results (SEER) registry (20182021). Patients treated with RT alone (n = 1077) were compared to those receiving RT + CT (n = 4663). Kaplan-Meier analysis and Log-rank tests were performed. Results The estimated 3 years overall survival (OS) and cancer-specific survival (CSS) rates were 34.9% and 42.8%, respectively. Median OS and CSS were 21 and 28 months, respectively. Univariate analysis indicated that age, gender, T stage, pathological type and treatment option were independent prognosticators of OS and CSS. Multivariate analysis demonstrated that age, gender, T stage, N stage, and therapeutic strategy were correlated with OS, while gender, T stage, N stage and treatment option were independent prognostic factors for CSS. Subgroup analyses demonstrated that combining RT with CT improved OS in all patient subgroups, and improved CSS in all patients except those at stage N0. Conclusion In patients aged ≥65 years with stage III inoperable NSCLC from the SEER database, treatment with RT plus CT provided longer OS and CSS compared to RT alone, except for patients with N0 stage disease.